The Effect of Soldier Marching, Rucksack Load, and Heart Rate on Marksmanship. (March 2017) - Tenan, Matthew S.; LaFiandra, Michael E.; Ortega, Samson V.
Objective: The purpose was to determine if Soldier rucksack load, marching distance, and average heart rate (HR) during shooting affect the probability of hitting the target. Background: Infantry Soldiers routinely carry heavy rucksack loads and are expected to engage enemy targets should a threat arise. Method: Twelve male Soldiers performed two 11.8 km marches in forested terrain at 4.3 km/hour on separate days (randomized, counterbalanced design). The Rifleman load consisted of protective armor (26.1 kg); the Rucksack load included the Rifleman load plus a weighted rucksack (48.5 kg). Soldiers performed a live-fire shooting task (48 targets) prior to the march, in the middle of the march, and at the end of the march. HR was collected during the shooting task. Data were assessed with multilevel logistic regression controlling for the multiple observations on each subject and shooting target distance. Predicted probabilities for hitting the target were calculated. Results: There was a three-way interaction effect between rucksack load, average HR, and march ( p = .02). Graphical assessment of predicted probabilities indicated that regardless of load, marching increases shooting performance. Increases in shooting HR after marching result in lower probability of hitting the target, and rucksack load has inconsistent effects on marksmanship. Conclusion: Early evidence suggests that rucksack load and marching may not uniformly decrease marksmanship but that an inverted-U phenomenon may govern changes in marksmanship. Application: The effects of load and marching on marksmanship are not linear; the abilities of Soldiers should be continuously monitored to understand their capabilities in a given scenario.